Antimicrobial Resistance and the Spectrum of Pathogens in Dental and Oral-Maxillofacial Infections in Hospitals and Dental Practices in Germany - Meinen, Annika; Reuss, Annicka; Willrich, Niklas; Feig, Marcel; Noll, Ines; Eckmanns, Tim; Al-Nawas, Bilal; Markwart, Robby (Frontiers in Microbiology, 2021)
Data on microbiological profiles in odontogenic infections are scarce. This study aimed to analyze the spectrum of pathogens and antimicrobial resistance in clinical isolates from dental and oral-maxillofacial clinical settings in Germany. We analyzed 20,645 clinical isolates (dental practices: n=5733; hospitals: n=14,912) from patients with odontogenic infections using data (2012-2019) from the German Antimicrobial-Resistance-Surveillance (ARS) system. A total of 224 different species from 73 genera were found in clinical isolates from dental practices, and 329 different species from 97 genera were identified in isolates from hospital patients. In both hospitals and dental practices Streptococcus spp. (33% and 36%, respectively) and Staphylococcus spp. (21% and 12%, respectively) were the most frequently isolated microorganisms. In Streptococcus spp. isolates from hospitals, penicillin and aminopenicillin resistance proportions were 8.0% (95%CI 4.7-14.9%) and 6.9% (95%CI 4.7-9.9%), respectively. Substantially lower resistance proportions of penicillin and aminopenicillin were observed in dental practices (2.6% [95%CI 1.4-4.7%] and 2.1% [95%CI 1.1-4.0%], respectively). Among Staphylococcus aureus isolates from hospital patients methicillin resistance proportions were 12.0% (95%CI 9.7-14.8%), which was higher than in isolates from dental practices (5.8% [95%CI 4.1-8.1%]). High clindamycin and macrolide resistance proportions (>17%) were observed in Streptococcus spp. and Staphylococcus aureus isolates. In Klebsiella spp. isolates carbapenem resistance proportions were <1%. In sum, substantial antibiotic resistance was observed in isolates from odontogenic infections, which calls for strengthened efforts in antibiotic stewardship and infection prevention and control measures in both hospitals and dental practices.